PENDAMPINGAN BRANDING PRODUK BERBASIS KEKAYAAN INTELEKTUAL MELALUI KEPEMILIKAN MEREK DAGANG DAN DESAIN INDUTRI PADA RINTISAN BISNIS SEPATU RANGE DE CULTURE - Ipung Kurniawan Yunianto; Rendya Adi Kurniawan; Basnendar Herry Prilosadoso; Pisteo Gabriel Tori; Fatika Fajar Priana; Erlyana Zuar Dini (Abdi Seni, 2024)
This research examines the significance of trademarks and industrial designs as visual identities and value-added elements for Micro, Small, and Medium Enterprises (MSMEs). Trademarks serve to differentiate products and function as a marketing strategy, while industrial designs enhance the commercial value of products. This assistance program aims to raise legal awareness among MSMEs regarding trademarks and industrial designs, specifically focusing on the shoe products of Range de Culture (RDC). The primary challenge MSMEs face is a lack of understanding regarding the urgency of such intellectual property protection. The methods employed include education on the strategic role of trademarks and industrial designs in business competition and guidance throughout the registration process. As a result, RDC successfully registered its trademarks and industrial designs with the Directorate General of Intellectual Property (DJKI). This research highlights the importance of assisting in enhancing awareness and capacity among MSMEs to leverage intellectual property protection to bolster their competitiveness and business sustainability